2020
DOI: 10.9734/ajee/2020/v12i330160
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acoustical Performance of Residential Buildings for Sustainable Liveability and Satisfaction in Awka, Anambra State Nigeria

Abstract: This study assessed the acoustical performance of residential buildings in Awka, Anambra State to determine the level of satisfactions of the occupants. The study surveyed the residential buildings and distributed questionnaires to the users and occupiers of different classes of residential buildings. The results of the survey were analysed using Means Satisfaction Index (MSI) and Relative Performance Index (RPI) to assess the level of satisfaction of the occupants of the buildings and the acoustical performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This could be attested from the result, as their level of knowledge was limited to basic environmental performance criteria such as ventilation, visual comfort and utility. Secondly, most of the occupants were renters and do not have any input in the design and construction of the building they live in [85]. Besides, home owners are more likely to express satisfaction with their houses than tenants [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attested from the result, as their level of knowledge was limited to basic environmental performance criteria such as ventilation, visual comfort and utility. Secondly, most of the occupants were renters and do not have any input in the design and construction of the building they live in [85]. Besides, home owners are more likely to express satisfaction with their houses than tenants [59].…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that the occupant perceived satisfaction is positively related to the building performance criteria. A related study carried out by [85] on acoustical performance of residential buildings in Awka, Anambra State to determine the level of satisfactions of the occupants also revealed that the overall acoustic performance of the buildings was grossly poor and unsatisfactory, and that the occupant level of satisfaction was positively related to the acoustic performance of the buildings. Despite the foregoing results, studies dealing with application and occupant satisfaction of bioclimatic design and construction strategies in modern residential buildings in South-eastern Nigeria are grossly inadequate.…”
Section: Literature Reviewmentioning
confidence: 97%